Effects of protein levels and energy sources in total mixed ration on feedlot performance and carcass quality of Kamphaeng Saen steers - Boonsaen, Phoompong; Soe, Nann Winn; Maitreejet, Wisut; Majarune, Sutisa; Reungprim, Taweeporn; Sawanon, Suriya (Agriculture and Natural Resources, 2017)
The effects of dietary protein and energy sources of a total mixed ration (TMR) were evaluated based on the performance, carcass quality and production cost of feedlot Kamphaeng Saen steers. Twenty-four Kamphaeng Saen steers were assigned according to a 2 x 2 factorial in a randomized complete block design with two factors: 1) energy sources comprised of cassava chip (cTMR) and cassava chip plus ground corn (ccTMR); and 2) crude protein (CP) levels (12%CP and 14%CP). The steers were slaughtered after being fed for 120 d. The carcass characterization and meat quality were determined at day 7 of aging. The results indicated that the average daily gain, final weight (p < 0.05), carcass weight (p = 0.06) and the profit of the steers fed the cTMR were greater compared to the ccTMR without effects on carcass characteristic and meat quality. The different levels of CP in the diet had no effects (p > 0.05) on feedlot performance, carcass characteristic and meat quality but steers fed 12%CP cTMR provided a profit. Cassava chip provided good potential to be used as an energy source in a TMR for feedlot cattle.